Text and authority in the older Upaniṣads - Cohen, Signe (Brill's Indological library ;, 2008)
This book offers a new interpretation of the older Upani?ads. Issues of textual authority in the Upani?ads are examined, and the book also outlines a theory of textual criticism as applied to oral texts.